Induced Pluripotent Stem Cells and Outer Retinal Disease - Jin Yang; Bingcui Cai; Patrick Glencer; Zhiqing Li; Xiaomin Zhang; Xiaorong Li (Stem Cells International)
The retina, which is composed of multiple layers of differing cell types, has been considered the first choice for gene therapy, disease modeling, and stem cell-derived retinal cell transplant therapy. Because of its special characteristics, the retina, located in the posterior part of the eye, can be well observed directly after gene therapy or transplantation. The blood-retinal barrier is part of a specialized ocular microenvironment that is immune privileged. This protects transplanted cells and tissue. Having two eyes makes perfect natural control possible after a single eye receives gene or stem cell therapy. For this reason, research about exploring retinal diseases’ underlying molecular mechanisms and potential therapeutic approach using stem cell technique has been developing rapidly. This review is to present an up-to-date summary of the iPSC’s sources, variations, differentiation methods, and the wide-ranging application of iPSCs-RPCS or iPSCs-RPE on retinal disease modeling, diagnostics, and therapeutics.